Coordination training of sportsmen, specializing in sport kinds of gymnastic - I.A. Tereshchenko; A.P. Otsupok; S.V. Krupenya; T.M. Liauchuk; V.N. Boloban (Physical Education of Students)
Purpose: experimental substantiation of effectiveness of coordination training program, worked out for sportsmen, specializing in sport kinds of gymnastic. Material: In the research first year students (21 persons: 14 girls and 7 boys of age 17-18 years) participated. All they specialized in sport kinds of gymnastic. From them there were 15 masters of sports and 6 candidate masters of sports. Results: students’ sensor motor coordination was confidently increased by means of realization of program of exercises for perfection of static-dynamic and static-kinetic stability. Conclusions: we recommend new direction of specific exercises’ realization; exercise, developing and improving static-dynamic and static-kinetic body balance. Coordination training of sportsmen, specializing in sport gymnastic shall take one of priority places in system of physical education and sport training means.